Perencanaan Tebal Perkerasan Kaku (Rigid Pavement) Pada Ruas Jalan Jatirejo - Mojokerto (STA 0+100 - 10+100) - Kefin Putra; Bambang Suprapto; Azizah Rachmawati (Jurnal Rekayasa Sipil, 2020)
In line with the passage of time and service life, road condition in the end will runinto decrease, both in terms of service level and structural conditions. The increasein traffic volume will cause a decrease in services due to decrease road capacity.This will cause the level of road saturation to increase, so that the road is unableto serve the community and is not according to need. Traffic volume density due totoo narrow roads, frequent road damage due to excessive vehicle loads, andfrequent inundation when it rains due to poor drainage systems. LHR data, CBRdata, Rainfall data, and Contour Maps as a basis for planning thick existing rigidpavement. The length of the road worked is 10 km with a road width of 6 m. With aplanned age of 20 years, traffic development is 3.1%, and thickness for widening ofthe rigid pavement is 22 cm. With a square shape obtained 4 types of channeldimensions a.) H = 1.3 m; b = 0.50 m; b.) H = 1.44 m; b = 0.55 m; c.) H = 1.6 m;b = 0.65 m; d.) H = 0.3 m; b = 0.50 m can accommodate runoff water in the Jatirejoroad section in Mojokerto Regency.Keywords: Rigid Pavement Planning, Drainage, Jatirejo.